Emerging Ophthalmic Complications regarding Digital Eye Strain, Diabetic Retinopathy, and Refractive Errors. A Clinical Study - Saira Bano, Abdul Haleem, Dolat Singh Sodho, Amir Zeb Khan, Anwar.Ul.Haq, Tahir Mahmood Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the relation of digital device usage, diabetic retinopathy, and refractive error as well as the predictors of severe digital eye strain (DES) in a clinical population. Methods: Sixty patients (mean age 41.3 ± 10.2 years; 46.7% male, 53.3% female) were subjected to comprehensive ocular examination including visual acuity, refractometry, slit lamp bio-microscopy and fundus photography. A validated questionnaire was used to assess digital device usage, and glycemic control was assessed in the diabetic patients. Independent predictors of severe DES were identified by multivariate logistic regression. Results: 70% of patients used digital devices for more than 4 hours per day, and 65% had DES symptoms. Diabetes was present in 33.3% of the cohort, and 60% of diabetics had poor glycemic control (HbA1c >8.0%). Of these patients, 75% had refractive errors, including 55% myopia. Multivariate analysis confirmed digital device usage longer than 4 hours a day (OR = 2.9; 95% CI: 1.2–7.0; p = 0.016) and poor glycemic control (OR = 3.2; 95% CI: 1.1–9.3; p = 0.031) as independent significant predictors of severe DES with female gender and myopia marginally significant. Conclusion: Prolonged digital device exposure and poor glycemic control are strongly associated with severe DES, advanced diabetic retinopathy, and myopic progression. In the digital era, ocular health will depend on integrated strategies of digital hygiene and optimal metabolic management. Keywords: Digital Eye Strain; Diabetic Retinopathy; Refractive Errors; Myopia; Digital Device Usage; Glycemic Control; Ocular Health; Digital Hygiene